Consistency in valuation: A practical guide (2010)
Practitioners and teachers easily break some consistency rules when conducting or teaching valuation of assets, which may lead to different results by different methods. In this short note we present a practical guide to call attention to the most frequently broken consistency rules. Firstly, they have to do with the consistency in matching of the cash flows. Secondly, with the proper expression for the cost of levered equity, and different formulations for the weighted average cost of capital, for finite cash flows. Thirdly, with the consistency between the terminal value and growth. In this article we deal with the first two, and leave any considerations about terminal value for a subsequent note, considering for now the terminal value as given. We show that, keeping this consistency, all methods lead to the same value. We illustrate this by a simple example. In the Appendices we show some algebraic derivations. © 2010 de Cladea.